Husband Behavior in Supporting Immunization in Babies - Mohammad Riyad; Munir Salham; Sriwahyudin Moonti (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2023)
Immunization is the most important thing in an effort to protect children's health. Based on data obtained from Kotarindau Village, the working area of the Dolo Health Center, the majority of the coverage of immunization for infants is 66.7%. This shows that there are 33.3% of infants who have not received complete immunization. This type of research is descriptive quantitative research with a sample of 69 heads of families. Data were collected using a questionnaire. The analysis used in this research is univariate analysis. The results of univariate analysis showed that the distribution of 69 respondents who had good knowledge of immunization for infants was 38 people (55.07%) while those who were less well informed were 31 people (44.93%). While the distribution of attitudes that support as many as 37 people (53.62%) and attitudes that do not support as many as 32 people (46.38%). In conclusion, most of the heads of families or husbands who have good knowledge about giving immunizations to infants and most of the heads of families or husbands have a supportive attitude. It is recommended for the Dolo Health Center to further improve counseling about giving immunizations to babies so that family heads or husbands who have babies in the Dolo Health Center work area, Sigi Regency to be more proactive in improving their abilities so that they can be more prepared and be more supportive of giving immunizations to babies.